Tompinai Co. / Anastasia Diasip ... [et al.] - Diasip, Anastasia; Mualasan, Faiezah Diyanah; Salim, Fatin Najihah; Jumper, Jacquelina; Jaffery, Maya Magdeline; Mat Azim, Natasya Aqilah (2016)
The name of our firm is Tompinai Co. It is a company that provides business consultation to those that demand for it. Business consultation is the need that most entrepreneurs would seek for upon commencing businesses. In starting any business or simply being involved in the business industry, a wise businessperson would prefer some proper guidance on how to start their business or in going through business ideas and plans. Our company would be offering consultation predominantly to local entrepreneurs that consist of mostly Bumiputeras as well as non-Bumiputeras and foreign entrepreneurs. This is not only to generally help entrepreneurs in Kota Kinabalu area but also offer assistance for the potential local businessmen to undertake business ventures of their own as well as developing better Bumiputeras' involvements in business commerce. Henceforth, the term "Tompinai" as our company's name that means brothers and sisters in one of Sabah's native language, Kadazandusun. The nature of our business is partnership. Our office is located at Cyber Square 2, Penampang. The date expected to start up our business is in June 2016. The growth of businesses around Kota Kinabalu has been increasing over the years ranging from so called hipster cafes and coffee shops to real estate properties development. Therefore, we are look at it as an opportunity to establish in a business consultation industry. Since our target market consists of increasing numbers of entrepreneurs in Kota Kinabalu and eventually some more coming from other parts of the Malaysia along with businesspersons overseas, the business has a high potential to expand. From this, the prospect of our business in the future is to have increased 3% and 5% of our business sales on the second and third year respectively.